Women Detention and Incarceration in China: The 2010 Bangkok Rules, Domestic Humanitarian Values, and Legal-Political Priorities. (6th July 2018) - Cheng, Lei; Nesossi, Elisa
Abstract: This article examines law, practice, and ideas concerning detention and imprisonment of women in the People's Republic of China (PRC). It is based on an empirical study we conducted at five research sites (two women's prisons and three pre-trial detention centres) in China in 2013. The analysis is based on the 2010 United Nations Rules for the Treatment of Women Prisoners and Non-Custodial Measures for Women Offenders (Bangkok Rules). Issues surrounding the detention and imprisonment of women have been addressed only marginally by the existing literature, both within and outside China, marking our article as a valuable contribution. Our central argument is that in the PRC, the issue of women's deprivation of liberty demonstrates a latent tension between two key sets of values. On the one hand, it reflects the humanitarian and paternalistic ethos that have traditionally characterized the treatment of women within the Chinese justice system since ancient times. On the other, it responds to politically led priorities organized around ideas of justice efficiency and the maintenance of social stability as mirrored by existing legislation. Our empirical research highlights that this area of justice administration is scarcely regulated. Special provisions have only been made regarding pregnant and breastfeeding women, separate custody and control, the location for the construction of women's prisons, and other limited areas. The few provisions in the legislation show a heightened degree of awareness that women have unique needs and vulnerabilities and deserve special treatment and protection. However, since the law lacks specificity, it is left to the discretion of local authorities to interpret and implement it in accordance with local circumstances. Authorities struggle to find a balance between the need to protect women and their unique needs and the need to ensure order and security among the population of women inmates.